Surface localization of CdZnS quantum dots onto 2D g-C3N4 ultrathin microribbons: Highly efficient visible light-induced H2-generation. (August 2016) - Yao, Lihua; Wei, Ding; Ni, Yuanman; Yan, Dongpeng; Hu, Changwen
Abstract: The construction of new semiconductor photocatalysts toward high-efficiency splitting water has played an important role in developing sustainable and clean hydrogen energy. In this work, new type of micro/nano-sized hybrids were synthesized based on the assembly of 0D Cd0.5 Zn0.5 S quantum dots (QDs, size: ca. 5 nm) onto 2D graphitic carbon nitride ( g -C3 N4 ) ultrathin microribbons (thickness: ca. 4 nm) via an in-situ growth hydrothermal method. The Cd0.5 Zn0.5 S 32 wt%@C3 N4 composite exhibits the highest visible-light-driven H2 -generation rate of 33.41 mmol h −1 g −1 without any noble-metal as cocatalyst, and the apparent quantum efficiency is 46.65% at 450 nm. Such H2 -generation rate is higher than the pristine g -C3 N4 and Cd0.5 Zn0.5 S by a factor of 27.39 and 9.18 respectively, which is significantly enhanced compared with most as-reported noble-metal-free semiconductor catalysts to date. In addition, compared with the pristine Cd0.5 Zn0.5 S, the photocatalytical stability of Cd0.5 Zn0.5 S QDs@C3 N4 is highly improved. The enhanced H2 -generation performance can be attributed to the well-matched energy level and strong electronic coupling between two components at the g- C3 N4 interface as well as enhanced visible-light absorption. The uniform dispersion of Cd0.5 Zn0.5 S QDs onto the g -C3 N4 ultrathin microribbons also facilitates the depression of electron-hole recombination from potential aggregation of Cd0.5 Zn0.5 S. Therefore, this work supplies an effective way to obtain promising 2D micro/nanostructures for high-efficiency visible light-induced H2 -generation. Graphical abstract: Highlights: New type of g -C3 N4 microribbons were synthesized vis pyrolysis, thermal exfoliation and liquid exfoliation process. 0D CdZnS quantum dots were localized on 2D g -C3 N4 ultrathin microribbons, which show high efficient H2 -generation under visible-light irritation without any noble-metal. Compared with pure CdZnS, the composite photocatalyst of CdZnS quantum dots and g -C3 N4 ultrathin microribbons displayed excellent photocatalytic stability.